2019
DOI: 10.1088/1742-6596/1294/5/052001
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative coupling of Amoxicillin using 4-Aminoantipyrine: Stability and higher sensitivity.

Abstract: Amoxicillin (AMX) is a semi-synthetic β-lactam antibiotic belonging to the group of penicillins. When ingested, it is partially (about 80–90%) excreted as chemically unchanged via faeces and urine into the domestic sewage and thence discharged to the wastewater treatment plants, which subsequently, removing this substance from the aqueous solution is important. Therefore, the aim of current study was to determine the effects of different optimum conditions of the oxidative coupling calorimetric methods for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 10 publications
0
7
0
2
Order By: Relevance
“…lnq e ¼ lnK F þ ð1=nÞ lnC e (10) ln ðq RP :K RP C e q e À 1Þ ¼ lnK RP þ b lnC e (11) Where C e (mg/L) and q e (mg/g) are the concentration and sorption capacity, respectively, at equilibrium. qmax (mg/g) is the maximum adsorption capacity and b is the Langmuir constant.…”
Section: Effect Of Initial Concentration and Adsorption Ishotermsmentioning
confidence: 99%
See 2 more Smart Citations
“…lnq e ¼ lnK F þ ð1=nÞ lnC e (10) ln ðq RP :K RP C e q e À 1Þ ¼ lnK RP þ b lnC e (11) Where C e (mg/L) and q e (mg/g) are the concentration and sorption capacity, respectively, at equilibrium. qmax (mg/g) is the maximum adsorption capacity and b is the Langmuir constant.…”
Section: Effect Of Initial Concentration and Adsorption Ishotermsmentioning
confidence: 99%
“…It is known that AMX degrades very little and bioaccumulates in the environment. [8,10] It is known that amoxicillin contained in pharmaceutical wastewater has a toxic effect on many organisms in the food chain and inhibits the photosynthetic mechanisms of organisms. [11] Harmful effects such as endocrine disruption and growth inhibition on aquatic and terrestrial ecosystems have been found to occur in the environment where amoxicillin is present.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Son yıllarda yapılan bilimsel çalışmalar, ilaç endüstrisine bağlı ilaç tüketimi artışının, özellikle sucul ortamlarda, küresel ölçekte yeni toksik kirletici sorununu ortaya Amoksisilin (AMX), penisilin grubuna ait β-laktam antibiyotikleri içerisinde en sık kullanılan ilaç etken maddedir [10]. Bu ilaç etken maddeler, gram pozitif bakterileri etkilemenin ötesinde, gram negatif basillere karşı anti-bakteriyel enfeksiyon tedavisinde sıklıkla kullanılır [11].…”
Section: Introductionunclassified
“…Sci. 2022;11(1), 031-038 D. Öztürk, H. Mıhçıokur, kimyasal olarak değişime uğrar (metabolize olur) ve idrar ya da dışkı yoluyla kanalizasyona karışır [10]. Kanalizasyona karışan AMX, konvansiyonel atıksu arıtma tesislerinde çok az miktarda (%0.09) biyolojik bozunmaya uğrayarak alıcı ortamlara deşarj edilir [12].…”
Section: Introductionunclassified